Modelling the potential of rainwater harvesting to improve the sustainability of landscape and public garden irrigation - Jacque, Hugo; Knox, Jerry W.; Gush, Mark B.; Holman, Ian P. (Elsevier, 2023)
Access to water for irrigating amenity landscape and public gardens is under intense pressure due to the rising competition for water between different sectors, exacerbated by increased drought risk and climate change. Rainwater harvesting (RWH) has the potential to reduce the economic impacts of restrictions on irrigation abstraction in dry years and to build resilience to future water shortages. This study investigated the hydrological viability of RWH for the landscape and public garden sector based on an analysis of five Royal Horticultural Society gardens. A RWH model was developed and combined with on-site observations, key informant interviews and GIS analyses, to estimate irrigation demands and the volumes of harvested rainfall for contrasting agroclimatic years. The results showed that gardens located in wetter regions and with low irrigation water demand to harvestable area ratio had a higher RWH potential and could almost exclusively rely on rainwater to meet irrigation demand, even in dry years. RWH potential is more limited for gardens in drier regions where they would require larger areas to harvest rainwater and for storage. Appropriately designed rainwater harvesting systems offer the potential to remove most of the risk of irrigation abstraction restrictions during dry years and associated impacts on amenity planting quality and visitor experience.
Keywords: irrigation efficiency; model; rainfall; reservoir; water saving